2021
DOI: 10.1109/access.2021.3131481
|View full text |Cite
|
Sign up to set email alerts
|

Dual Active Compensation for Voltage Source Rectifiers Under Very Weak Grid Conditions

Abstract: DC subgrids consisting of modern active loads (ALs) and local dc distributed generation (DG) units are normally interfaced with the main ac grid by utilizing bidirectional voltage source converters (VSCs). Under the very weak grid (VWG) conditions, the integration of voltage-oriented controlled (VOC) VSCs in the inversion mode becomes very challenging and therefore undamped oscillations in the power and angle responses are yielded. Most of the existing works address this issue for VSCs in the inversion mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, this study only investigated the low-frequency instability mechanism and the CSCR for inverter or rectifier operation was not identified. In [34], it was shown that VSC stability under a weak grid is more critical under rectifier operation. A VSC is stable for a wider range of SCR under inverter operation than rectifier operation.…”
mentioning
confidence: 99%
“…However, this study only investigated the low-frequency instability mechanism and the CSCR for inverter or rectifier operation was not identified. In [34], it was shown that VSC stability under a weak grid is more critical under rectifier operation. A VSC is stable for a wider range of SCR under inverter operation than rectifier operation.…”
mentioning
confidence: 99%